Agricultural sector proposals - Chesney, H.A.D. (CCS GeorgetownGY, 1993)
Looks at the importance of the agricultural sector, and the emerging problems, challenges and opportunities. Analyses the major problems conforming the private sector, and identifies investment opportunities. Highlights two specialized agricultural regional institutions - the Caribbean Agricultural Research and Development Institute (CARDI) and the Caribbean Feed Corporation (CFC).